Integrating probabilistic risk analysis into property investment appraisal: evidence from Nigeria - Nnamani, O. C.; Onyekwelu, E. I.; Anih, S. C.; Egbo, P. N.; Ajah, J. N. (International Journal of Real Estate, 2025)
This study examines the integration of probabilistic risk analysis into residential property investment appraisal in Nigeria; addressing the dominance of deterministic valuation techniques in emerging markets. Using a 15-year discounted cash flow (DCF) model and a case study of a six-unit block-of-flats residential property in Enugu, the research combines sensitivity analysis, scenario technique, and Hillier’s standard deviation model into a unified “3S Risk Process Model.” The approach quantifies investment uncertainty by generating probability distributions of returns and estimating the likelihood of achieving a target rate of return. Results identify target rate of return (TRR) and rental growth as the key determinants of investment performance, with a 61.03% probability of meeting the 10.5% TRR, indicating moderate risk exposure. The study demonstrates that probabilistic analysis provides a more rigorous and transparent framework for decision-making, offering implications for valuers, lenders, and policymakers seeking to strengthen evidence-based investment appraisal and promote resilience in Nigeria’s real estate sector.
Keywords: Risks; Risk analysis; Investment appraisal; Property investment; Nigeria